The theology of liberalism: political philosophy and the justice of God - Nelson, Eric (The Belknap Press of Harvard University Press, 2019)
Pelagian origins -- Representation and the fall -- "The bargain basis": Rawls, anti-Pelagianism, and moral arbitrariness -- Egalitarianism and theodicy -- Justice, equality, and institutions -- "God gave the world to Adam, and his posterity in common": appropriation and the Left-Libertarian challenge -- Conclusion: Back to representation